“I’m Managing My Diabetes between Two Worlds”: Beliefs and Experiences of Diabetes Management in British South Asians on Holiday in the East—A Qualitative Study - Neesha R. Patel; Anne Kennedy; Christian Blickem; David Reeves; Carolyn Chew-Graham (Journal of Diabetes Research)
Background. Diabetes is disproportionately high among British South Asians compared to the general UK population. Whilst the migrant British South Asians group has received most attention on research related to diabetes management, little consideration has been given to impact of travel back to the East. This study aimed to explore the role of social networks and beliefs about diabetes in British South Asians, to better understand their management behaviours whilst holidaying in the East. Methods. Semistructured interviews were conducted in Greater Manchester. Forty-four participants were recruited using random and purposive sampling techniques. Interviews were analysed thematically using a constant comparison approach. Results. Migrant British South Asians expressed a strong preference to be in a hot climate; they felt they had a healthier lifestyle in the East and often altered or abandoned their diabetes medication. Information acquisition on diabetes and availability of social networks in the East was valued. Conclusion. Social networks in the East are a valued source of information and support for diabetes. The lack of adherence to medication whilst abroad suggests that some migrant British South Asians have a poor understanding of diabetes. Future research needs to explore whether patients are seeking professional advice on diabetes management prior to their extended holiday.